Poligami Kiai Madura (Kajian Fenomenologis Hakikat Poligami Dalam Pandangan Kiai Madura) - Ah. Kusairi; Abdul Mukti Thabrani (Fakultas Syariah IAIN Madura, 2022)
Polygamy is one of the most debated and scrutinized topics in marriage. This study examines the values of polygamy in the practice of cultivating polygamous marriages among Kyai in Madura. This study seeks to address the reasons and purposes of polygamy among Kyai in Madura, the perspective of the Madurese Kyai on the nature of polygamy, and the spiritual significance of polygamy for the Kyai of Madura. The methodology employed in this study is qualitative phenomenology research. This study reaches the following conclusions: (1) The kiai's motivation for practicing polygamy is to maintain the continuity of lineage or lineage, (2) The spiritual values of polygamy that the Kyai of Madura are convenience and blessing of obtaining food, (3) The Kyai's justification as destiny for explaining the spiritual significance of spiritual needs.